State-legal protection of entrepreneurs’ rights in public legal relations - E. B. Abakumova (Russian Journal of Economics and Law, 2018)
Objective: comprehensive analysis of the state legal protection of the rights of entrepreneurs in public relations.Methods: reliability of the study and validity of the author’s arguments are provided by the use of both empirical and theoretical methods of cognition (description, analysis, synthesis, induction, deduction). In addition to general scientific methods, the paper used special legal research methods: formal-legal and comparative-legal.Results: the article actualizes the theoretical and practical issues of state legal protection of the rights of entrepreneurs in relations with state and municipal authorities. The study focuses on the analysis of competence of the main elements of the state human rights mechanism in relation to business entities, in which the key role belongs to the institution of business ombudsmen, the judiciary bodies and the Prosecutor’s Office. The measures taken by the state in the recent years, aimed at strengthening the rule of law in the legal relations under consideration, including the establishment of the institution of business ombudsmen, special units to monitor the observance of the entrepreneurs’ rights in the Prosecutor’s Offices, as well as granting of additional powers to the Prosecutor’s Office, indicate a trend towards increasing the effectiveness of the human rights protection mechanism. Scientific novelty: the author proposes her own definition of the concept of the state-legal mechanism for the protection of entrepreneurs’ rights, which is understood as a set of complementary means (legal, administrative, economic, etc.), by which the state exerts an impact on legal relations between subjects of law in order to protect the rights and legitimate interests of entrepreneurs. The paper also considers the structure of the above-mentioned mechanism, identifies its main elements and their role at the present stage of development of human rights protection of the state, and identifies the actual problems of its functioning. Practical significance: the theoretical provisions presented in this article expand knowledge about the nature and content of the state legal protection of the entrepreneurs’ rights in the Russian Federation. The results of the study can be used in legislative and law enforcement practice for further improvement of legal regulation and institutional support of the state-legal mechanism of the entrepreneurs’ rights protection.